Gender Stereotypes in The Five Year Engagement Movie - Latifatus Zuhro (Pioneer: Journal of Language and Literature, 2018)
Gender stereotypes are broad categories which reflect the impressions and beliefs about appropriate behavior for women and men. The issue of gender stereotypes still exists today, and the society wants to understand that gender stereotypes can have an important influence on career and relationships. The data in this research were in the form of dialogues, and behaviours of characters in The Five Year Engagement movie. This research was done by analyzing the data qualitatively. The steps of data analysis consisted of sorts the data that were related with gender stereotypes theory, classified the scenes of dialogue and behavior, and described how gender stereotypes were reflected based on the types of basic kinds and types of stereotypes based on the role in The Five Year Engagement movie. The result of the research described basic kinds of gender stereotypes, there were four data indicated personality traits, five data for domestic behaviours, two data for occupation, and four data for physical appearance. Then, these data were classified into types of gender stereotypes based on the roles, there were seven data for masculinity, five data for feminity, and five data found of androgyny. Based on the analysis, the dominant types of gender stereotypes based on the roles was masculinity which had eight data.